Sensor and Survey Measures Associated With Daily Fatigue in HIV: Findings From a Mixed-Method Study. (January 2020) - Makic, Mary Beth; Gilbert, Danielle; Jankowski, Catherine; Reeder, Blaine; Al-Salmi, Nasser; Starr, Whitney; Cook, Paul F.
Abstract: Fatigue is the most common symptom among people living with HIV (PLWH), but may have many causes. This mixed-method study was designed to characterize PLWH's fatigue experiences and associated self-management behaviors, using Two Minds Theory. Fifty-five PLWH completed daily smartphone surveys on psychological states and fatigue at random times for 30 days and used a Fitbit Alta™ wristband. Within-person multilevel models were used to identify univariate correlates of fatigue. The first 25 participants also completed qualitative interviews about their experiences, and results were compared across methods. Participants had significant fatigue despite well-controlled HIV. Fatigue varied between persons and over time. Fatigue was associated with physical activity, sleep, daily psychological states, and barriers to self-care. PLWH reported new insights into fatigue from self-monitoring. There are potential opportunities for PLWH to improve sleep, activity, or stress management to alleviate fatigue. PLWH were interested in reducing fatigue and willing to use self-monitoring technology.